THE ROLE OF THE INTELLIGENCE UNIT OF THE INTAN JAYA POLICE IN HANDLING ARMED GROUPS IN THE INTAN JAYA DISTRICT AREA - Sigit Prasetyo, Tatag; Soekorini, Noenik; Ayuningtyas, Fitri; Hamdani, Fathul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
A Police Security Intelligence (Intelkam) acts as the "eyes and ears" in early detection and anticipation of threats to security and public order (Kamtibmas). One of the main challenges faced is the armed criminal group (KKB) in Intan Jaya Regency, Central Papua, which often terrorizes civilians and armed contact with security forces. KKB aims to separate Papua from the Unitary State of the Republic of Indonesia. This research aims to analyze the role and strategy of the Polres Intelkam unit in handling KKB in Intan Jaya. The method used is empirical legal research, which examines facts based on interviews and observations of police actions in dealing with this separatist group. The results showed that Intan Jaya Police implemented a mobilization strategy by working with community, religious and traditional leaders to build social resilience against the influence of separatism. In addition, Intelkam carries out the functions of investigation, security, and mobilization in its operations, both open and closed. In conclusion, the Intan Jaya Police Intelkam strategy plays an important role in creating conducive conditions and stemming the influence of KKB in the community through security and community approaches.